(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that the implementation of public administration in the regions is a complex and multifaceted process, because the imperfection of the structural reform of the Ukrainian economy is manifested precisely at the regional level. In view of this, a properly organized system of civil protection, which embodies modern trends in the development of society and the state, and is also capable of providing protection to the population in the light of current security challenges, becomes especially important during the development of the regions. Attention is focused on the need to consider modern globalization transformations, as well as the ontological, epistemological and axiological nature of the principles themselves, their connections with human existence, as well as their orientation to protecting the interests of the public when understanding the phenomenon of principles of law. It is noted that the field of civil protection in the regional context is undergoing significant changes, the influence of new factors, a deep understanding of which reveals fundamentally new principles of civil protection at the regional level, among which the principle of caution is singled out and analyzed; the principle of social responsibility of citizens, public authorities, enterprises, institutions and organizations; principle of clustering; the principle of international cooperation and the principle of using modern information technologies and continuous technological development in the course of ensuring civil protection at the regional level.